Implementasi Metode Additive Ratio Assesment (ARAS) Dalam Pemberian Promo Tiket Umroh Pada Member - Zaza Mutiara Arini; Mesran Mesran; Melda Panjaitan (Journal of Computer System and Informatics (JoSYC), 2023)
PT Anugerah Quba Mandiri (AQM) Tour & Travel every year has the charm to be able to attract the attention of customers or customers on the promo route. the selection of Umrah ticket promos held by the travel party is not given to all pilgrims who register for Umrah. The promo will be given only to pilgrims who get the general qualifications set by the company. Members who have been officially registered can have the opportunity to get a promo to be given to the selected congregation, but ticket promos can only be given to one congregation, therefore it must be based on the appropriate requirements and qualifications. Members who have registered will be recorded using a computer system to record the number of members who are entitled to the ticket promo. With the large number of registered members, the company really needs a decision system that can help in making decisions on ticket promotions. A Decision Support System (SPK) that can help companies find out which members are eligible for ticket promotions using the Additive Ratio Assessment (ARAS) method. The ARAS method is a method or method of decision making that uses the concept of utility degree ranking by comparing the overall index value of each alternative to. In its implementation, the decision support system in providing promos to PT AQM tour & Travel members uses the ARAS method, obtaining effective and objective ranking results. From the results of research conducted at PT AQM Tour & Travel it can be concluded that Alternative A13 on behalf of Nurlela Br Sitepu is stated as a member who gets an Umrah ticket promo with a preference value of 0.2963.